Wellness and healthy programme for KOM Staff(WELLKOM) - Zakaria, , Rosini; Md Aris, Mohd Aznan; Draman, Samsul; Abdullah, Fa’iza (2012)
KOM Wellness and Healthy programme, abbreviated as WELLKOM, was initially planned as a health awareness programme that will also serve as a platform for Kulliyyah of Medicine (KOM) staff to release his or her mind, body and soul after a whole week of strenuous academic and administrative activities. The main objective of the programme is to improve the health and well-being of KOM staff through health activities that will support positive lifestyle changes thereby resulting in improved staff productivity. Another objective is to improve the ‘ukhuwah’ between KOM staff at the two campuses in Kuantan i.e. the Indera Mahkota Campus and the Jalan Hospital Campus. This programme can also serve as a channel to update staff on current KOM activities through announcements at the end of the sessions. The programme is open to all KOM staff (Academic and Non-Academic) without any fee being incurred on them. The budget for the programme is obtained from the Kulliyyah to spend for the instructor fee and also for the preparation of light refreshments after each session. The programme started off with an aerobic session on 28 October 2011 and it was conducted by a competent male instructor. The response was very good and we appreciate the cooperation given by the Heads of Departments for releasing their staff to participate in this programme. WELLKOM will be an on-going programme and will be conducted twice every month (Friday, first and third weeks) between 8.30 am until 9.30 am. Other activities that have been planned include jogathon, group cycling and indoor games like netball, volley ball, badminton and table tennis. Inter-departmental social matches are also planned and this can be a channel for selection and short-listing of potential players for the annual Staff Games.